Aktivitas Gelatinase Bakteri Endogen Maggot Black Soldier Fly (Hermetia illucens) pada Hydrolyzed Collagen (HC) yang Berasal dari Limbah Pengolahan Ikan Tuna: Gelatinase Activity of Endogenous Bacteria of Maggot Black Soldier Fly (Hermetia illucens) on Hydrolyzed Collagen (HC) Derived from Tuna Fish Processing Waste - Ismi, Alfita Ramdiyati; Aisah, Aisah; Sheptiriani, Amelia Firdia; Nada, Qatrun; Syaputri, Fauzia Ningrum; Pertiwi, Wulan; Amelia, Rena Pitri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Hydrolyzed collagen (HC) is an enzymolyzed collagen or gelatin product and has a small molecular weight (0.3-8 kDa). HC can be produced enzymatically with protease enzymes. The methods used in HC production include isolation of gelatinase-producing bacteria from BSF maggots, gelatin extraction from tuna fish waste, gelatinase activity screening, gelatinase enzyme production, HC production, and confirmation analysis. Bacterial isolation resulted in 22 bacterial colonies, 3 of which had gelatinase activity as observed from the activity screening results. The yield of gelatin extract obtained was 9.36%. HC production was obtained as much as 10 mL with the addition of 5% crude gelatinase enzyme. The SDS-PAGE results can be determined that there is a band with a size of 31-42 kDa, it shows that the gelatinase can be isolated. Keywords: hydrolyzed collagen, maggot BSF, tuna fish, gelatinase, gelatin Abstrak Hydrolyzed collagen (HC) merupakan produk kolagen atau gelatin yang terenzimolisis dan memiliki ukuran berat molekul yang kecil (0,3-8 kDa). HC dapat diproduksi secara enzimatik dengan enzim protease. Metode yang digunakan dalam produksi HC antara lain adalah isolasi bakteri penghasil gelatinase dari maggot BSF, ekstraksi gelatin dari limbah ikan tuna, skrining aktivitas gelatinase, produksi enzim gelatinase, produksi hydrolyzed collagen, dan analisis konfirmasi. Isolasi bakteri didapatkan koloni bakteri sebanyak 22 koloni, 3 diantaranya memiliki aktivitas gelatinase yang diamati dari hasil skrining aktivitas, Rendemen ekstrak gelatin yang didapatkan adalah 9,36%. Produksi HC didapatkan sebanyak 10 mL dengan penambahan 5% crude gelatinase enzyme. Hasil SDS-PAGE dapat ditentukan bahwa terdapat pita pada ukuran 31-42 kDa, hal ini menunjukkan bahwa gelatinase dapat terisolasi. Kata Kunci: hydrolyzed collagen, maggot BSF, ikan tuna, gelatinase, gelatin